Disaster Communication in Sleman Regency: Evaluating the SIMANTAB Application's Implementation and Impact - Nurjanah, Adhianty; Prawoto, Nano; Apriliani, Riski; Nabilazka, Chalila Raihan (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2024)
Indonesia, located in the Pacific Ring of Fire, is highly vulnerable to natural disasters, particularly volcanic eruptions. The Yogyakarta Province, including Sleman Regency, regularly faces threats from Mount Merapi eruptions. This research aims to analyze the integration of disaster communication in Sleman Regency through a cultural approach and the utilization of the SIMANTAB (Sleman Disaster Resilience Information System) application. Using a qualitative case study method, data were collected through in-depth interviews with the Regional Disaster Management Agency (BPBD), local communities, and residents. The findings reveal that BPBD Sleman successfully integrates technology and local cultural values in crafting effective disaster communication messages. The SIMANTAB application is used as the primary tool in disaster mitigation and management, particularly for Mount Merapi eruptions, while still respecting local wisdom and involving community leaders. This digital innovation aligns with E-Government principles while preserving cultural values in message delivery. Strong leadership commitment, collaboration with media actors, and ongoing training and support for the community enhance preparedness for emergency situations. This study underscores the importance of integrating cultural and technological approaches to strengthen sustainable disaster communication strategies that are responsive to community needs.Keywords: Disaster Communication, SIMANTAB Application, Merapi Mount AbstrakIndonesia, terletak di wilayah cincin api Pasifik, memiliki risiko tinggi terhadap bencana alam, terutama erupsi gunung berapi. Provinsi Yogyakarta, termasuk Kabupaten Sleman, secara rutin menghadapi ancaman erupsi Gunung Merapi. Penelitian ini bertujuan untuk menganalisis integrasi komunikasi bencana di Kabupaten Sleman melalui pendekatan budaya dan penggunaan aplikasi SIMANTAB (Sistem Informasi Sleman Tangguh Bencana). Menggunakan metode kualitatif dan studi kasus, data diperoleh melalui wawancara mendalam dengan Badan Penanggulangan Bencana Daerah (BPBD), komunitas lokal, dan masyarakat. Hasil penelitian menunjukkan bahwa BPBD Sleman berhasil menggabungkan teknologi dan budaya dalam menyusun pesan komunikasi bencana yang efektif. Aplikasi SIMANTAB digunakan sebagai alat utama dalam mitigasi dan penanggulangan bencana, khususnya terkait erupsi Gunung Merapi, dengan tetap mempertimbangkan kearifan lokal dan peran tokoh masyarakat. Inovasi digitalisasi ini sejalan dengan prinsip E-Government, namun tetap mempertahankan nilai budaya dalam penyampaian pesan. Komitmen pemimpin daerah, kolaborasi dengan media, serta pelatihan dan pendampingan kepada masyarakat memperkuat kesiapan menghadapi situasi darurat. Penelitian ini menegaskan pentingnya integrasi budaya dan teknologi dalam memperkuat strategi komunikasi bencana yang berkelanjutan dan responsif terhadap kebutuhan masyarakat.Kata Kunci: Komunikasi Bencana, Aplikasi SIMANTAB, Gunung Merapi